Memberdayakan UMKM Lokal Wilayah Solok Melalui Sistem E-commerce Opencart untuk Meningatkan Penjualan - Wulandari, Mely; Annas, Firdaus; Rahmi, Miftahur (JOVISHE : Journal of Visionary Sharia Economy, 2024)
Micro, small, and medium enterprises (MSMEs) play a crucial role in the local economy, including in the Solok region. However, challenges such as limited market access, low adoption of digital technology, poor digital literacy, and resource constraints often hinder their progress. This study aims to empower local MSMEs in Solok by creating an E-commerce system based on OpenCart. This initiative will enhance sales, expand market reach, and promote digital inclusion in the industry. Using a qualitative approach, this research employs a research and development (R&D) methodology, implemented through the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). During the analysis phase, data were collected through in-depth interviews with MSME actors, observing business processes, and reviewing literature on E-commerce technology. The analysis identified key needs, including ease of use, catalog availability, secure online payment methods, shipment tracking, and systematic sales reporting. The E-commerce system is built using the OpenCart platform, known for its exceptional flexibility and various built-in features that integrate with third-party services. Expected benefits include increased market reach, enhanced competitiveness of local products in the digital market, and higher MSME revenues. By implementing promotional features and discounts, the system allows customers to interact directly with sellers and facilitates online collaboration among businesses, leading to more effective marketing. Thus, this research supports the digital transformation of MSMEs, particularly in Solok, addressing challenges in the digital era.